Asuhan Keperawatan Pada Tn. A Dengan Gangguan Defisit Perawatan Diri : Kebersihan Diri / Mandi, Berhias Dan Berpakaian Di Ruang Sadewa RSJ Daerah Surakarta - Pradhitama, Nanda Bayu, Arif Widodo, A.Kep., M.Kes (2015)
Background : Mental health is a condition in which an individual can develop physically, mentally, spiritually and socially so that the individual is aware of his own abilities, can cope with the problem and are able to provide the ability to group. In 2013 the numbers have experienced problems of mental disorders reaches 25% and 1% of them have experienced severe mental disorder. In Indonesia, the average - average severe mental disorders such as hallucinations, delusions, thinking ability, impaired thought processes and strange behavior, for example in Central Java disorders of 2.3% by weight. Based on these problems the authors are interested to provide nursing care to patients with mental disorders, especially in clients with self-care deficit to maintain personal hygiene to the client in the room Sadewa Mental Hospital of Surakarta. Aim of Research : To know the nursing care to clients with self-care deficit disorder. Result : Having done using the strategy of implementation of nursing care to clients with impaired self-care deficit, the result the client can establish a trusting relationship, the client can menggenal about the importance of personal hygiene, the client can perform personal hygiene with the help of nurses, clients can perform personal hygiene independently , the client can maintain personal hygiene independently. Conclusion : Nursing problems clients on Self Care Deficit, basically can be performed well and most of the problems can be resolved with the help of nurses Key words : Deficit Care, Nursing Care